Seven red flags for internships and work experience in top professional sport - Anderson, N.; Close, B.; Easdale, K. (British Journal of Sports Medicine, 2020)
When does a rewarding and mutually beneficial internship or work experience morph into an unethical employment practice? Internships can expose a junior practitioner to high-profile settings and aid in building clinical skills, deepen knowledge and broaden their network. These true gains will bolster the intern`s resume, particularly if the mentor is a senior clinician. The price for what is essentially advanced, specific training is that the intern work at a reduced salary or pro bono.